Science and Social Anthropology: Resolving Hierarchical and Horizontal Knowledge Structures - Rose, James W. W. (Vilnius University Open Series, 2025)
The relationship between social anthropology and the so-called ‘natural’ sciences has a long and fraught history, beginning with the field’s inception in the 1870s. Despite periodic attempts at thematic reinvention, social anthropology consequently remains trapped in what has been termed a ‘pre-paradigmatic’ state, without consensus among social anthropologists on either a self-consistent object of study for their field, parameters of study, or a causal model for explaining that object. Pedagogic sociology offers a causal explanation for this lack of integration, by describing how formal education systems define and segregate ‘natural’ and ‘social’ sciences, and by further describing a mechanism for achieving desegregation. Corroborating observations made by both natural scientists and social anthropologists, this chapter uses a pedagogic sociological model to describe the lack of integration between natural and social science generally, and between natural science and social anthropology in particular. This pedagogic sociological model is then used to describe a potential pathway towards a resolving integration between social anthropology and natural science, with reference to incipient formal empirical methods and to Cultural Model Theory.